2014
DOI: 10.1021/tx500046k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Microglia from Adult Mouse Brain: Selected Applications for ex Vivo Evaluation of Immunotoxicological Alterations Following in Vivo Xenobiotic Exposure

Abstract: Microglia play a dual role in neuroprotection as well as in neurodegeneration and thus occupy the focal interest in neurodegenerative disease research. In vitro studies either by using cell lines or neonatal mouse primary microglia correlated xenobiotic induced microglial activation and neuronal death. However, these in vitro studies cannot portray the in vivo scenario. Therefore, environmental pollutant induced in vivo alteration in microglial function can be best assessed by ex vivo analysis, which is not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
5
20
0
Order By: Relevance
“…Second, it has been reported that CSDS causes neuroinflammation throughout the brain, including the prefrontal cortex and amygdala [79]. This finding is likely to support our data in the ex vivo microglial response to LPS reflecting the inflammatory response profiles of microglia in the whole brain [11, 46, 47, 80]. However, further studies on whether kososan extract affects stress-induced neuroinflammation in other brain regions are needed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Second, it has been reported that CSDS causes neuroinflammation throughout the brain, including the prefrontal cortex and amygdala [79]. This finding is likely to support our data in the ex vivo microglial response to LPS reflecting the inflammatory response profiles of microglia in the whole brain [11, 46, 47, 80]. However, further studies on whether kososan extract affects stress-induced neuroinflammation in other brain regions are needed.…”
Section: Discussionsupporting
confidence: 85%
“…Microglia were isolated from adult testing mouse whole brain except the cerebellum as described previously [11, 46, 47] with some modifications. Briefly, following decapitation, the whole brain except the cerebellum was readily extracted and chopped finely with a fine sharp scissor in ice-cold serum-free Dulbecco’s modified Eagle’s medium (DMEM)/F12 (Sigma) containing papain (20 U/ml, Worthington Biochemical Corporation, Lakewood, NJ, USA), DNase I (2 mg/ml, Sigma), and 1% penicillin/streptomycin (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Splenocytes were seeded at a density of 0.1 × 10 6 cells/200 µl/ well in 96 well culture plates and incubated in the absence or presence of concanavalin A (ConA) (2.5 µg/ml; Sigma) in a 5% CO 2 incubator at 37 °C for 72 h. Culture supernatants were collected and pooled from each treatment group, and secreted cytokines were measured in supernatant plated in triplicate using a Milliplex mouse cytokine assay kit as previously described 59 in Bio-Plex MAGPIX multiplex reader (Bio-Rad). Fluorescence associated with different antibody-coated magnetic beads was read to quantitate respective cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that arsenic alters the functions of microglia, which are the resident macrophages found in the central nervous system [12,13]. The metalloid notably increased ex-vivo secretion of IL-6 and TNF- from microglia isolated from mice exposed for 7 days to 0.38 mg/kg arsenite [12]. In vitro, the supernatant of arsenic-exposed-microglial cultures induced murine neuronal cell death [14].…”
Section: Macrophages and Dendritic Cells (Dcs)mentioning
confidence: 99%